Impunidad penal de los menores adultos e incidencia en la seguridad social, en la ciudad de Machala, provincia de El Oro, en el año 2012. - Bravo Herrera, Jaime Manuel (2012)
Our society is struck down by the constant criminal aggression plaguing our city and the whole country, scourge that unfortunately coming to violate the rights of our children and adolescents are not as passive illicit dl, but rather as active participants in the commission of attacks against the law, in any form we know. There is no theory with which we can define what is an adolescent offender, peormente trying to explain that commit crimes, if it comes in many cases well-trained homes, parents and respectable families, will be perhaps the stage that we are living is the one that is causing many adolescents commit crimes, but it is clear that like everything in life changes, many parents say let pass they are things of youth, worse than it actually does not understand is that we are projecting that our children continue diverting their road, pitifully along a route that will not lead to safe harbor.